An experimental study on the kinetics of leaching for the preparation of a Raney-Silver catalyst - Salt, I; Gültekin, S (SPRINGER, 2004)
A Raney-Ag catalyst was prepared by leaching out aluminium from a Raney Ag-Al alloy with NaOH solution. The kinetics of leaching has been investigated in a stirred-batch-reactor at various temperatures by using alloy particles of different sizes. The kinetic model best fitting the experimental results has been determined.
Keywords: Raney Ag-Al alloy; electrocatalyst; leaching; noncatalytic fluid-solid heterogeneous reaction; Chemistry